Characterizing highly fibrillated nanocellulose by modifying the gel point methodology. (1st January 2020) - Sanchez-Salvador, Jose Luis; Monte, M. Concepción; Batchelor, Warren; Garnier, Gil; Negro, Carlos; Blanco, Angeles
Highlights: Aspect ratio of highly fibrillated nanocellulose is estimated using the gel point methodology. Crystal Violet dyes nanocellulose improving the sediment visualization. Controlling sedimentation time is essential for consistent gel point measurement. Flocculation is not required to determine gel point of charged nanocellulose. Abstract: The characterization of nanocellulose fibres (NC) length is a difficult and indirect measurement which relies on aspect ratio calculation and fibre diameter analysis. The aspect ratio can be directly calculated from the gel point, a parameter obtained from sedimentation experiments. The gel point has been used with macroscopic fibres and microfibrillated cellulose, that easily sediment by gravity. However, this methodology has not yield consistent results with highly charged nanofibres nor with fibres with sediment layer difficult to observe. In this study, the gel point methodology is modified: 1) dying the fibres with Crystal Violet to enable the visualization of the fibrils sedimentation line without affecting the fibre network; and 2) by optimizing the sedimentation time to ensure complete settling. The two types of fibrils characterized -low and high fibrillated NC (LF-NC, HF-NC)- behave differently due to the slower sedimentation of HF-NC. The time to reach a stable sedimented layer increases with the level of fibre fibrillation, the charge and the decrease of fibre dimension. Reproducible gel point can be measured after 2 days for LF-NC; however, 8 days are required for HF-NC. The modified methodology was validated by quantifying the influence of pH and salt concentration. As expected, low pHs and the addition of CaCl2 coagulate HF-NC into flocs which increase the ratio: final over initial fibres height (Hs /Ho ); this decreases significantly the gel point, as a lower amount of HF-NC are required to interconnect all fibres. This modified method is a valuable tool for the accurate dimensional characterisation of highly charged and low diameter cellulose nanofibres.